The Effect of AI-Based Adaptive Learning Approach, Learning Satisfaction on Learning Outcomes of ISE Class X SMAN Ngoro - Lala Erika; Munawaroh (IKIP PGRI Bojonegoro, 2026)
This research is motivated by the low learning outcomes of ISE subjects in class X of SMAN Ngoro and the demand for the use of artificial intelligence-based learning technology in improving the quality of learning processes and outcomes. The purpose of this study is to analyze the influence of AI-based adaptive learning approach and learning satisfaction on student learning outcomes in ISE class X subjects of SMAN Ngoro. This study uses a quantitative approach with an ex post facto design, the population of all students of class X and a sample taken with the techniques described in the proposal, using questionnaires and grade documentation as data collection instruments. Data was analyzed using inferential statistical techniques according to a procedure that has been designed to test the hypothesis of the influence of each independent variable and its simultaneous influence on learning outcomes. The expected results show that AI-based adaptive learning and learning satisfaction have a positive and significant effect on learning outcomes, so that it can be the basis for the development of economic learning innovations in high school.